2020
DOI: 10.7759/cureus.9924
|View full text |Cite
|
Sign up to set email alerts
|

Nontyphoidal Salmonella as a Cause of Mediastinal Abscess in a Patient With Extensive Cardiac Surgery

Abstract: Focal infections caused by nontyphoidal Salmonella (NTS) are relatively rare and usually self-limited. Those with cardiac surgical history are predisposed to intrathoracic seeding, including mediastinal infections and abscesses. We report a case of a 39-year-old Hispanic male with a complex past medical history of Tetralogy of Fallot with an initial presentation of Salmonella gastroenteritis and concern for sepsis. The patient did not clinically improve on ceftriaxone despite appropriate cultures and susceptib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 17 publications
(19 reference statements)
0
1
0
Order By: Relevance
“… 8 NTS has been shown to have a predilection for the endovascular environment. 9 A report from Hibbert et al 10 showed there is a tendency of developing endovascular infection in NTS. This patient had a positive NTS and a history of CABG.…”
Section: Discussionmentioning
confidence: 99%
“… 8 NTS has been shown to have a predilection for the endovascular environment. 9 A report from Hibbert et al 10 showed there is a tendency of developing endovascular infection in NTS. This patient had a positive NTS and a history of CABG.…”
Section: Discussionmentioning
confidence: 99%